The Influence of Learning Orientation on Performance of Micro and Small Agro-processing Enterprises in Tanzania (International Journal of Scientific Research and Management (IJSRM), 2022)
Firms that operate in dynamic and competitive business environment require strong learning orientation to build competitive edge and accelerate their performance. This study examines the influence of learning orientation on performance of micro and small agro-processing enterprises in Tanzania. Learning view holds that, organizations that can learn the business environment are in a better position to perform than their rivals. However, there exists scant literature on the relationship between learning orientation and performance specifically in micro and small agro-processing enterprises in developing economies like Tanzania. The current study put forward to contribute to the existing knowledge with empirical evidence relating the learning orientation dimensions of commitment to learning, open-mindedness and shared vision with firm performance. The study adopted a cross-sectional survey design whereby data were collected through structured questionnaire from 302 agro-processing firms in Dar es Salaam, Morogoro and Arusha regions in Tanzania. The analysis was carried through Structural Equation Modeling with SPSS IBM AMOS software version 21. The findings revealed that, all three constructs of learning orientation have positive significant influence on the firm performance. This suggests that, the agro-processing MSEs should strengthen their learning orientation for better business performances. Besides, the policies related to agro-processing should provide enabling environment for the small firms to learn and build their competitiveness for the improved performances.